I am courage : a book of resilience - Verde, Susan (Abrams Books for Young Readers, 2021)
Celebrates everyday courage, including believing in ourselves, speaking out, trying new things, asking for help, and getting back up no matter how many times we may fall. Includes information on how to let go of fear by practicing yoga poses and mindful breathing exercises.